The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4238/2012.may.21.5
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTM1 and GSTT1 with ageing in auto repair shop workers

Abstract: ABSTRACT.We evaluated the possible influence of glutathione S-transferase mu (GSTM1) and glutathione S-transferase theta (GSTT1) genes on genetic damage due to occupational exposure, which contributes to accelerate ageing. This study was conducted on 120 car auto repair workshop workers exposed to occupational hazards and 120 controls without this kind of exposure. The null and non-null genotypes of GSTM1 and GSTT1 genes were determined by multiplex PCR. Micronucleus frequency, Comet tail length and relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In the same study population, GSTT1 and GSTM1 polymorphisms showed significant differences in DNA damage markers in buccal cells between workers and controls 31. Previous studies have demonstrated that GSTM1 enzymes protect cells against oxidative stress, and lack of GSTM1 enzymes increases oxidative DNA damage in smokers 32.…”
Section: Tl and Exposure To Environmental And Occupational Chemicalsmentioning
confidence: 71%
See 1 more Smart Citation
“…In the same study population, GSTT1 and GSTM1 polymorphisms showed significant differences in DNA damage markers in buccal cells between workers and controls 31. Previous studies have demonstrated that GSTM1 enzymes protect cells against oxidative stress, and lack of GSTM1 enzymes increases oxidative DNA damage in smokers 32.…”
Section: Tl and Exposure To Environmental And Occupational Chemicalsmentioning
confidence: 71%
“…The glutathione S-transferase (GST) genes, including GSTT1 , GSTM1 and GSTP1 , play an important role in detoxifying xenobiotics 31. In the same study population, GSTT1 and GSTM1 polymorphisms showed significant differences in DNA damage markers in buccal cells between workers and controls 31.…”
Section: Tl and Exposure To Environmental And Occupational Chemicalsmentioning
confidence: 93%
“…Several studies support our results. Eshkoor et al (2012) found a higher prevalence of the GSTT1 null genotype (62.5%) in Malaysia. A lower prevalence was described by Nelson et al (1995), and only 9.7% of Mexican-Americans analyzed in the city of Boston had the null polymorphism of the GSTT1 gene.…”
Section: Discussionmentioning
confidence: 82%
“…GSTM1 and GSTT1 enzymes decrease oxidative damage and prevent induced genotoxic attacks on DNA [ 52 ]. Many studies have explored the role of GSTM1 and GSTT1 polymorphisms in the genotoxic damage and telomere length [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%